NEO QUADRATUM GEOMETRICUM: Inovasi Instrumen Falak Klasik George Von Peurbach - 'Alamul Yaqin (ELFALAKY: Jurnal Ilmu Falak, 2023)
Quadratum Geometricum is a surveying and astronomical instrument by George Von Peurbach who is known as an Austrian astronomer. This article discusses the accuracy and development concept of Quadratum Geometricum which is named Neo Quadratum Geometricum. This research is development research, which has 2 stages, namely the preliminary stage and the formative evaluation stage which consists of: self evaluation, prototyping (expert reviews and one-to-one, and small groups), and field tests. The findings of this study include: Neo Quadratum Geometricum innovation, namely the existence of a conversion arc from the value of the horizontal and vertical rulers which serves to value of the angle of tan/cotan immediately known without looking at the table. Quadratum Geometricum is more accurate in the tan angle conversion test, Neo Quadratum Geometricum is 0.0025 greater than the calculator, while Quadratum Geometricum is the same. Because, the accuracy of Neo Quadratum Geometricum is only up to minutes. However, in terms of the effectiveness of using Neo Quadratum Geometricum it is more practical, because it does not use tables. In measuring the height of the object, the difference is 8.5 cm from the actual height.